ANTESEDEN PEMBELIAN IMPULSIF DI PASAR RITEL MODERN : PEMBELAJARAN DARI INDONESIA - Dodi Ria Atmaja; Alvin Edison (JURNAL LENTERA BISNIS, 2022)
The development of the industry retail modern is growing rapidly causing significantchanges to people's lives, especially in terms of shopping. The convenience ofshopping has an impact on people who are increasingly making impulsive buying.This study aims to determine the effect of brand image, situational factors, salespromotion and store atmosphere on impulsive buying mediated by hedonic shoppingmotivation at retail modern market. In this study, the population studied were allpeople who had go or had purchased at least once at retail modern market in WestJakarta. The sample in this study amounted to 200 peoples using purposive samplingtechnique. The data is then processed using the Structural Equation Model Lisrel(SEM) method. Based on the test results, it is known that brand image, situationalfactors, sales promotion and store atmosphere have a significant effect on hedonicshopping motivation. While brand image, situational factors, hedonic shopping salespromotion and store atmosphere motivation have a significant effect on impulsivebuying.Keywords: Brand Image, Situational Factors, Sales Promotion, Store Atmosphere,Impulsive Buying and Hedonic Shopping Motivation